13C MRS of human brain at 7 Tesla using [2‐13C]glucose infusion and low power broadband stochastic proton decoupling. Issue 3 (27th April 2015) - Li, Shizhe; An, Li; Yu, Shao; Ferraris Araneta, Maria; Johnson, Christopher S.; Wang, Shumin; Shen, Jun
Abstract : Purpose: Carbon‐13 ( 13 C) MR spectroscopy (MRS) of the human brain at 7 Tesla (T) may pose patient safety issues due to high radiofrequency (RF) power deposition for proton decoupling. The purpose of present work is to study the feasibility of in vivo 13 C MRS of human brain at 7 T using broadband low RF power proton decoupling. Methods: Carboxylic/amide 13 C MRS of human brain by broadband stochastic proton decoupling was demonstrated on a 7 T scanner. RF safety was evaluated using the finite‐difference time‐domain method. 13 C signal enhancement by nuclear Overhauser effect (NOE) and proton decoupling was evaluated in both phantoms and in vivo. Results: At 7 T, the peak amplitude of carboxylic/amide 13 C signals was increased by a factor of greater than 4 due to the combined effects of NOE and proton decoupling. The 7 T 13 C MRS technique used decoupling power and average transmit power of less than 35 watts (W) and 3.6 W, respectively. Conclusion: In vivo 13 C MRS studies of human brain can be performed at 7 T, well below the RF safety threshold, by detecting carboxylic/amide carbons with broadband stochastic proton decoupling. Magn Reson Med 75:954–961, 2016. © 2015 Wiley Periodicals, Inc.